Rate of elimination of radioiodineavid lymph node metastases of differentiated thyroid carcinoma by postsurgical radioiodine ablation - Ilhan, Harun; Mustafa, Mona; Bartenstein, Peter; Kuwert, Torsten; Schmidt, Daniela (Nuklearmedizin - NuclearMedicine, 2016)
SPECT/CT detects radioiodine-positive cervical lymph node metastases (LNMs) of differentiated thyroid carcinoma (DTC) at the time of postsurgical radioablation (RA). Preliminary evidence indicates that the majority of LNMs are successfully treated by RA. The aim of this study was to confirm this evidence in a bicentric setting and to evaluate whether size is a predictor for successful elimination. Patients and methods: Since 01/2007 and 05/2008, respectively, SPECT/spiral-CT is performed routinely in all patients with DTC at RA in two University Clinics. The outcome of iodine-positive LNMs identified by SPECT/CT until 12/2012 was analyzed by follow-up diagnostic 131I scans and serum thyreoglobulin (Tg) values. LNM volume and short-axis diameter were evaluated as prognostic factors by a receiver-operating characteristic (ROC) analysis. Results: 79 patients with 97 iodine-positive LNMs were included. Surgery was carried out in 8 patients with 13 LNMs due to the presence of additional iodine-negative lesions. Of the remaining 84 LNMs, 74 (88%) were successfully treated as demonstrated by radioiodine scans at follow-up. 10 LNMs persisted. 67/70 LNMs smaller than 0.9 ml were treated successfully, whereas this was the case of only 6/14 exceeding this threshold. Using this cut-off level to predict treatment success, sensitivity, specificity, positive and negative predictive value were 92%, 73%, 96%, and 57%. Results for short-axis diameter (cut-off level < 1cm) were 90%, 69%, 94% and 56%. Conclusion: RA is effective in the treatment of the majority of 131I-positive LNMs identified in SPECT/CT images. In this study, 88% of iodine-positive LNM in DTC were successfully treated by radioiodine given at RA. Both LNM volume and diameter are reliable predictors of treatment success.
Keywords: Differentiated thyroid carcinoma; radioiodine; remnant ablation; lymph node metastases; elimination